Miłość, wybaczenie i ofiara. Obraz chrześcijaństwa w komiksowych wersjach Quo vadis - Górecka, Ewa (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
Quo Vadis, thanks to its plot structure, favours transformations – even into comic books, where the image of Christianity as an important aspect of the story is challenging to depict. It is therefore worth determining how religious issues are manifested in comic books related to the novel and how the culture in which they were conceived affected them. I reflect on the image of Christianity, recognising religion as a personal experience of each individual (W. James), especially one of love, forgiveness, and sacrifice. These values were given more attention by the Polish writers, and in both adaptations, the sequences and frames were formulated differently, they differed in terms of composition (different perspectives, plans, and use of text), and finally, both offered different interpretations of Sienkiewicz’s novel. The authors of the French adaptation read the book as a vibrant, adventure-history-love story, while the Polish authors saw it as a story dedicated to a moment in history in which one world ends and another one begins, as a new religion emerges. These interpretations confirm that culture plays an important role in how literary works are adapted into the comic book format.